Pangasius djambal gelatin increases osteoprotegerin, decreases RANK and RANKL after tooth extraction in vivo - Mardiyantoro, Fredy; Prasetyaningrum, Nenny; Hidayat, Lukman H.; Khasanah, Uswatun; Roring, Virginia C.; Muizun, Ahida; Kardikadewi, Varellia A. W. (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Osteoprotegerin (OPG) plays a role in preventing osteoclast formation and osteoclastic bone resorption by inhibiting the receptor activator nuclear factor-β and its ligand (RANK–RANKL) interaction that causes bone resorption. Pangasius djambal gelatin contains essential amino acids that may stimulate bone remodeling. Purpose: This study aimed to investigate the expressions of OPG, RANKL, and RANK following tooth extraction to ascertain whether OPG is associated with the RANKL and RANK ratios following gelatin induction. Methods: This study was a true experimental study with a simple, randomized post-test only control group design. Twenty-four albino rats (Rattus norvegicus) were divided into two groups (n = 4). The treatment group was treated with P. djambal gelatin following tooth extraction, while the control group was left untreated. Animal models undergoing tooth extraction were anesthetized intraperitoneally with ketamine (1,000 mg/10 ml up to 0.2 ml). The tooth was then extracted slowly so as not to break it. P. djambal gelatin was dripped (0.1 ml) into the socket after the extraction procedure. The association of OPG with RANKL and RANK immunohistochemistry expressions was evaluated after three, five, and seven days. Results: There was a significant increase in OPG expression on day 7 (P < 0.05) and a significant decrease in the expression of RANKL and RANK (P < 0.05) in the treatment group. Conclusion: The application of P. djambal gelatin could increase OPG expression, decrease RANKL and RANK expression in the socket following tooth extraction, and might be associated with the inhibition of bone resorption.